Social Media Comments As Forensic Linguistic Corpus In Cybercrime Handling: A Systematic Literature Review - Mochammad Alif Risqullah; Mila Rosmaya; Priati Assiroj (Universitas Muhammadiyah Ponorogo, 2026)
The rise in popularity of social media has increased the arena for cybercrime activities, especially with the presence of digital comments including hate speech, defamation, and information that may violate the Electronic Information and Transaction Law (UU ITE) of Indonesia. This paper presents a Systematic Literature Review (SLR), using the PRISMA 2020 approach, focusing on forensic linguistic approaches applied on social media comments as a data corpus for cybercrime. Literature reviews have been performed on four different databases, which are Google Scholar, Garuda, Scopus, and DOAJ, from the year 2015 to 2024. Out of 172 reviewed papers, only 18 of them have fulfilled the inclusion requirements. Based on synthesis results, the conclusions are that: (1) the two main approaches used in forensic linguistics are lexical semantic and speech act pragmatics; (2) Instagram is the most explored platform in terms of the corpus of data; (3) most of the papers have mapped the results with UU ITE Article 27, 28, and 45; and (4) there is still a lack in the studies related to multimodality and standardization of digital evidence extraction procedures as legally acceptable evidence.